A Comparative Evaluation of Antimicrobial Efficacy of Five Different Herbal Solutions: Propolis, Azadirachta Indica (Neem), Triphala, Green Tea, and Turmeric against Enterococcus Faecalis and Debris Removal from the Root Canal Using Two Irrigation Protocols—Manual and Ultrasonic—An Ex Vivo Study - Omni P. Jain; Ronel Lairenlakpam; Pallavi Priya; Vidhur Chouhan; Karishma Anand; Deepika Dhandoria (Journal of Pharmacy and Bioallied Sciences)
Aim: To assess the objectives are to assess and contrast the antibacterial activity of neem, propolis, triphala, turmeric, and green tea as well as the effectiveness of these substances in clearing root canal debris in the presence and absence of passive ultrasonic irrigation. Methodology: Techniques, such as neem, propolis, triphala, turmeric, and green tea, were tested for antibacterial activity using enterococcus faecalis (ATCC-24212) as a test organism and an agar diffusion test. The negative control group was saline. Results: A total of 240 removed human mandibular permanent teeth were utilized to assess the effectiveness of the debris removal process. From the CEJ, they received decoronation. After that, they were split into 12 smaller groups based on whether passive ultrasonic stimulation was employed throughout the irrigation technique. Conclusion: Propolis and triphala had the highest antibacterial activity against enterococcus faecalis. Turmeric had the most efficiency in removing debris from the root canal, followed by propolis, and saline had the least amount. Using all six test irrigants, the debris removal effectiveness was increased by passive ultrasonic irrigation.